2018
DOI: 10.1093/milmed/usy033
|View full text |Cite
|
Sign up to set email alerts
|

The Voice of the Consumer: A Survey of Veterans and Other Users of Assistive Technology

Abstract: This survey revealed several themes for future research and development. Advanced wheelchair design, smart device applications, human-machine interfaces, and assistive robotics and intelligent systems emerged as priorities. Survey results also demonstrated the importance for researchers to understand the effects of policy and cost on translational research and to be involved in educating both consumers and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 22 publications
3
8
0
2
Order By: Relevance
“…Usability outcomes were the highest among perceptions of the technology's "innovative" appeal, as well as if the provider would "recommend" the technology to a fellow healthcare provider, or a patient with a TBI. The outcomes align with previous literature, which find general excitement about innovative aspects of Internet of Things (IoT), and VR based protocols, particularly when treating the cognitive and behavioral pathologies in Veterans (Dicianno et al, 2018;Kirsch, 2019). Furthermore, the innovative utility has been shown to work among older adults before, specifically with recalling tasks and specific details (Dicianno et al, 2018;Kirsch, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Usability outcomes were the highest among perceptions of the technology's "innovative" appeal, as well as if the provider would "recommend" the technology to a fellow healthcare provider, or a patient with a TBI. The outcomes align with previous literature, which find general excitement about innovative aspects of Internet of Things (IoT), and VR based protocols, particularly when treating the cognitive and behavioral pathologies in Veterans (Dicianno et al, 2018;Kirsch, 2019). Furthermore, the innovative utility has been shown to work among older adults before, specifically with recalling tasks and specific details (Dicianno et al, 2018;Kirsch, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…The outcomes align with previous literature, which find general excitement about innovative aspects of Internet of Things (IoT), and VR based protocols, particularly when treating the cognitive and behavioral pathologies in Veterans (Dicianno et al, 2018;Kirsch, 2019). Furthermore, the innovative utility has been shown to work among older adults before, specifically with recalling tasks and specific details (Dicianno et al, 2018;Kirsch, 2019). Such protocols add a safer element to rehabilitation, while offering an entertaining distraction to their symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…5,28 It is important to continue to follow the emergence of access technologies such as motor control via brain-computer interfaces, voice and eye activation, and face recognition, which may prove to be more efficient, and intuitive modes for individuals with severe physical and cognitive disabilities. 29 In some studies, 13,17 practice time has been identified as an important factor in proficiency. Other studies, 24 including the results of the current study, did not find significant associations between practice time and proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that children who require alternative access modes need different learning strategies or longer practice periods than currently provided because of sensorimotor integration factors and cognitive levels (perceiving and processing stimuli, motor planning, and appropriate reactions while moving in space) that impede their learning process . It is important to continue to follow the emergence of access technologies such as motor control via brain‐computer interfaces, voice and eye activation, and face recognition, which may prove to be more efficient, and intuitive modes for individuals with severe physical and cognitive disabilities …”
Section: Discussionmentioning
confidence: 99%
“…2,4,7 Both caregivers and care recipients prefer portable, powered technologies for transfers. 14,15 A robotic assisted transfer device (RATD) is one example. [16][17][18][19][20] The Strong Arm, an RATD attached to a power wheelchair, significantly lowered selfreported discomfort frequency and physical demand from caregivers compared with a mechanical floor lift (Fig.…”
mentioning
confidence: 99%